Estimation of the optimum propane content for the Spheripol Polypropylene process. (March 2021) - Hatzantonis, Hippocratis P.
Abstract: A Real Time Optimization (RTO) algorithm is proposed to optimize the reactors' propane content for the Spheripol Polypropylene process. This algorithm improves the present approach of arbitrarily selecting "optimum" propane values, based on monthly/yearly average balances. The optimum propane content depends on factors such as the costs of offgas and catalysts, the propane content in the feedstock and the catalyst mileage. The steady state process model is developed and tested over plant data to prove its predictive capabilities. Results from the off-line, as well as the in-line implementation of the algorithm are presented that demonstrate its applicability. Estimates on the amount of the expected savings for a medium size Polypropylene plant are also presented. Highlights: RTO Algorithm for the control of the propane content in a Spheripol Plant. A steady state process model is developed and tested over plant data. The RTO is applied to past plant data to estimate the propane deviation from the optimum. The algorithm is applied in-line and is proved to successfuly predict operator moves.